The Great Constantine and Athanasius. A Meeting between Two Different Worlds - Pavlov, Pavel (Forum Theologicum Sardicense, 2025)
Pavel Pavloff, The Great Constantine and Athanasius. A Meeting between Two Different Worlds. This paper presents the encounter between Constantine and Athanasius as an example of the collision between two worlds: Egyptian monasticism and the Roman state, which was already in the process of its irreversible Christianization.